2020
DOI: 10.3390/brainsci10100679
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Induced by Periodontal Inflammation Causes Neuroinflammation and Disrupts the Blood–Brain Barrier

Abstract: Background: Periodontal disease (PD) is a risk factor for systemic diseases, including neurodegenerative diseases. The role of the local and systemic inflammation induced by PD in neuroinflammation currently remains unclear. The present study investigated the involvement of periodontal inflammation in neuroinflammation and blood–brain barrier (BBB) disruption. Methods: To induce PD in mice (c57/BL6), a ligature was placed around the second maxillary molar. Periodontal, systemic, and neuroinflammation were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…To explain gliosis, they proposed a hypothesis that inflammatory cytokines and toxins damaged the BBB during the pathogenesis of periodontitis. Subsequently, another research group applied a 7-0 silk ligature, proved the hypothesis, and showed that the permeability of the BBB increased when periodontitis was induced in similar mice [118]. Moreover, if ligature placement was prolonged to one year, the mice showed signs of cognitive impairment in addition to neural inflammation [119].…”
Section: Effect On the Central Nervous Systemmentioning
confidence: 94%
“…To explain gliosis, they proposed a hypothesis that inflammatory cytokines and toxins damaged the BBB during the pathogenesis of periodontitis. Subsequently, another research group applied a 7-0 silk ligature, proved the hypothesis, and showed that the permeability of the BBB increased when periodontitis was induced in similar mice [118]. Moreover, if ligature placement was prolonged to one year, the mice showed signs of cognitive impairment in addition to neural inflammation [119].…”
Section: Effect On the Central Nervous Systemmentioning
confidence: 94%
“…; Sc, Streptococcus constellatus. References: [A] : Cardoso et al ( 2018 ); [B] : Bui et al ( 2019 ), [C] : Fine et al ( 2020 ), [D] : Gallimidi et al ( 2015 ), [E] : Ha et al ( 2015 ), [F] : Lamster and Pagan ( 2017 ), [G] : Jepsen et al ( 2020 ), [H] : Minty et al ( 2019 ), [I] : Torrungruang et al ( 2018 ), [J] : Suh et al ( 2019 ), [K] : Schenkein et al ( 2020 ), [L] : Singhal et al ( 2016 ), [M] : Cecoro et al ( 2020 ), [N] : Baeza et al ( 2020 ), [O] : Furutama et al ( 2020 ), [P] : Ferguson et al ( 2020 ) [Q] : Preshaw et al ( 2020 ), [R] : Sukumar and Tadepalli ( 2021 ), [S] : Badran et al ( 2020 ), [T] : Coke et al ( 2021 ), [U] : Han and Wang ( 2013 ), [V] : González-Febles and Sanz ( 2021 ), [W] : Maldonado et al ( 2020 ), [X] : Bunte and Beikler ( 2019 ), [Y] : Poole et al ( 2013 ), [Z] : Poole et al ( 2015 ), [Aa] : Stein et al ( 2012 ), [Ab] : Bobetsis et al ( 2020 ) .…”
Section: Medical Aspects Of Periodontal Inflammationmentioning
confidence: 99%
“…Sustained periodontal inflammatory states will alter the count of circulating neutrophils due to increased bone marrow output or mobilization of the marginal granulocyte pool (Cecoro et al, 2020 ). Uptake of advanced glycation end products (AGEs) during PD is reported to drive pro-inflammatory signals that, in turn, trigger redox-sensitive transcription factors deemed responsible for hyper-permeability of the endothelial cell, VCAM-1 (vascular cell adhesion molecule 1) activation, chemotaxis and the release of TNF, IL-1, IL-6 into the bloodstream (Furutama et al, 2020 ). These circulating inflammatory mediators are able then to modify endothelial function, leading to impaired vasodilation and causing significant alterations in the vascular structure (Cecoro et al, 2020 ).…”
Section: Medical Aspects Of Periodontal Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, there is a bidirectional intricate communication between the periphery and the CNS. In ammation in the periphery can interfere with the blood-brain barrier (BBB) integrity and induce changes in the brain [13,14].…”
Section: Introductionmentioning
confidence: 99%